Navigating Ethics in AI-Driven Translation for a Human-Centric Future: Menavigasi Etika dalam Penerjemahan Berbasis AI untuk Masa Depan yang Berpusat pada Manusia - Mohammed Kadhim Mutashar (Academia Open, 2024)
General Background: The rapid growth of AI technology is reshaping various industries, including translation, bringing both opportunities and ethical challenges. Specific Background: AI's integration into translation processes promises automation and efficiency but raises concerns about the role of human translators, translation quality, and cultural nuances. Additionally, issues like machine bias and privacy preservation are emerging as critical ethical considerations. Knowledge Gap: While much attention has been given to AI's technical advancements, there is a lack of comprehensive research addressing the ethical implications of AI in translation and its impact on professional roles and requirements. Aims: This study aims to critically review the literature on AI's impact on the translation profession and explore the ethical challenges arising from AI integration. It seeks to provide recommendations for ethical translation practices in an AI-enhanced environment. Results: Through in-depth interviews with professional translators, educators, and industry experts, the study identified key themes such as transparency in AI systems, the responsibility of human translators, bias in AI systems, and the impact on human translators. Novelty: This research offers a unique perspective by combining insights from diverse stakeholders and emphasizing ethical considerations in AI-assisted translation. It proposes an action-oriented approach to addressing ethical concerns to ensure the survival of the translation profession in an AI-driven society. Implications: The findings serve as valuable guidance for translators, educators, and policymakers, highlighting the need for ethical frameworks and guidelines specific to AI integration in translation. This study underscores the importance of balancing AI advancements with ethical standards to achieve high-quality, culturally sensitive translations. Highlight: Ethical Considerations: Address bias and privacy in AI-assisted translation. Human Expertise: Maintain human involvement for quality and cultural nuance. Future Research: Enhance ethical practices with diverse, comprehensive studies. Keyword: AI integration, translation ethics, machine bias, human translators, cultural sensitivity